2016
DOI: 10.1007/s12161-016-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Ultrasonic-Assisted Cloud Point Extraction with Flame AAS for Preconcentration and Determination of Trace Amounts of Silver and Cadmium in Dried Nut and Vegetable Samples

Abstract: In this article, ultrasonic-assisted cloud point extraction (UA-CPE) was used to the preconcentration of trace Ag(I) and Cd(II) in dried nut and vegetable samples. After ion association of Ag(I) and Cd(II) ions with 3,7-diamino-2,8-dimethyl-5-phenyl-phenaziniumchlorid (Safranin T) in the presence of excess potassium iodide (KI) at pH 6.0, the ternary complexes formed were quantitatively extracted into a micellar phase of poly(ethyleneglycol-mono-p-nonylphenylether) (PONPE 7.5) and then determined by flame atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that Ag I is more toxic than others chemical forms like AgNPs [95], so the determination and speciation of both is crucial to evaluate adequately the pollution caused by this element. When Ag is found in mg$L À1 -ng$L À1 concentration range, the analysis by standard analytical techniques such as AAS or ICP MS is not always possible [99,100]. Moreover, it is well known that the toxicity of Fig.…”
Section: Silvermentioning
confidence: 99%
“…Some studies have demonstrated that Ag I is more toxic than others chemical forms like AgNPs [95], so the determination and speciation of both is crucial to evaluate adequately the pollution caused by this element. When Ag is found in mg$L À1 -ng$L À1 concentration range, the analysis by standard analytical techniques such as AAS or ICP MS is not always possible [99,100]. Moreover, it is well known that the toxicity of Fig.…”
Section: Silvermentioning
confidence: 99%